Effect of treatment with pravastatin or ezetimibe on endothelial function in patients with moderate hypercholesterolemia - Grigore, L.; Raselli, S.; Garlaschelli, K.; Redaelli, L.; Norata, Giuseppe; Pirillo, A.; Catapano, A. (Springer, 2013)
Background/Aim: Statin treatment improves endothelial function. It is matter of debate, however, if this effect of statins is due to their action on low-density lipoprotein cholesterol (LDL-C) or to other non-lipidic (pleiotropic) effects. The aim of this study was to evaluate whether the effect of pravastatin on endothelial function is mediated by pleiotropic effects. We therefore compared the effect of pravastatin and ezetimibe, a cholesterol absorption inhibitor, at doses yielding similar reductions in LDL-C and examined the effect of the two treatments on flow-mediated dilation (FMD) in hypercholesterolemic subjects. Methods: A total of 33 moderately hypercholesterolemic patients were randomized into three treatment groups to receive ezetimibe 10 mg/day (n = 10), pravastatin 10 mg/day (n = 13) or no treatment (control, n = 10) for 6 weeks. To assess endothelial function, we determined FMD of the brachial artery non-invasively by high-resolution ultrasound before and after treatment. Results: Ezetimibe and pravastatin treatment reduced LDL-C (mean ± standard error) to a similar extent (-20.6 ± 4.1 vs. -24.1 ± 4.0 %, respectively; P = 0.4771), while no decrease was observed in the control group. FMD increased significantly after treatment with ezetimibe (from 11.4 ± 5.7 to 16.8 ± 3.6 %; P = 0.022) and with pravastatin (from 13.7 ± 4.9 to 17.5 ± 4.4 %; P = 0.0466), but not in the control group. There were no differences in the endothelial function changes between the two treatment groups. Conclusions: In this study, two treatments that lower cholesterol via different mechanisms improved endothelial function to a similar extent, suggesting that the observed effect can be explained by the reduction of cholesterol levels. © 2012 Springer-Verlag.